Trajectories of peripheral white blood cells count around the menopause: a prospective cohort study - Qiaoyun Dai; Yaya Zhang; Xiujuan Zhao; Xueying Yang; Huayu Sun; Shouling Wu; Shuohua Chen; Jianmei Wang; Zongfu Cao; Xu Ma (BMC, 2024)
Abstract Background Menopause significantly impacts the immune system. Postmenopausal women are more susceptible to infection. Nonetheless, the pattern of change in peripheral white blood cell counts around the menopause remains poorly understood. Methods We conducted a prospective longitudinal cohort study with repeated measurements using Kailuan cohort study of 3632 Chinese women who participated in the first checkup (2006-2007) and reached their final menstrual period (FMP) by the end of the seventh checkup (2018-2020). Peripheral WBC count indicators included total white blood cells (TWBC), neutrophils (NEUT), lymphocytes (LYM), and monocytes (MON). Multivariable mixed effects regressions fitted piece-wise linear models to repeated measures of WBC count indicators as a function of time before or after the final menstrual period (FMP). Interaction and subgroup analysis were used to explore the effects of age and body mass index (BMI) on changes in WBC indicators around FMP. Results WBC count indicators decreased before the FMP, and the reduction in TWBC, NEUT, and MON continued for 2 years following the FMP. LYM and NEUT declined during < -1 years and − 4 ∼ + 2 years relative to FMP, respectively. A reduction in MON was observed pre-FMP, extending continuously through the two-year period post-FMP. TWBC declined from − 3 to + 2 years relative to FMP, but both MON and TWBC increased during > + 2 years. The baseline age had an interaction effect on changes in WBC indicators during specific menopausal stages, except for TWBC. Individuals in different age subgroups showed distinct trajectories for NEUT, LYM and MON around the FMP. High baseline BMI had a synergistic effect on changes in specific menopause segments for TWBC, LYM, and MON. The impact of menopause on TWBC and LYM was postponed or counterbalanced in high BMI individuals. Individuals in three BMI subgroups experienced similar MON changes around FMP, and there were slight variations during < -4 years. Conclusions Menopause was associated with count changes of peripheral WBC. The trajectories of various WBC types differ around menopause. Age and BMI affected WBC trajectory around menopause. The menopause period may represent a window of opportunity to promote immune health in middle-aged women.